TRANSFORMATIONAL LEADERSHIP AND EMPLOYEE CREATIVITY: UNVEILING THE MEDIATING INFLUENCE OF ORGANIZATIONAL CULTURE AND LEARNING IN THE ESQ WORKPLACE - Widia Fatimah; Fanny Martdianty (RADJA PUBLIKA, 2025)
Employee creativity plays a pivotal role in enhancing organizational performance, serving as a key driver of innovation essential for sustaining competitiveness. In light of the decline in ESQ training participants over the past five years, strategic renewal is required to reignite interest, particularly by fostering employee creativity. This study examines the factors influencing employee creativity, focusing on transformational leadership, organizational culture, and organizational learning. Using a quantitative approach, data from 152 ESQ employees were analyzed with SEM LISREL 8.80. The results indicate that transformational leadership positively influences employee creativity through the mediating effects of the organizational culture dimensions attention to detail and teamwork/respect for people, while the dimensions of innovation and outcome orientation show no mediating impact. Additionally, organizational learning is found to positively mediate the relationship between transformational leadership and employee creativity.